Aptitude for Interpreting. - Pöchhacker, Franz (Benjamins current topics., 2014)
With increasing numbers of students wishing to become conference interpreters, but limited capacities in most university degree programs, accurate admission testing is an important means of predicting an applicant's chances of completing the program successfully. This article focuses on three aptitude tests for simultaneous interpretation: Pöchhacker's SynCloze test; Chabasse's cognitive shadowing test; and Timarová's personalized cloze test. The test battery was administered at the start of the 2009/2010 academic year to students beginning the two-year Master's program in conference interpret.